Association between Sella Turcica Morphology and Obesity in Adolescents - Karaman, Ahmet; Yasa, Yasin; Genc, Esra; Buyuk, S. Kutalmış (Journal of Dentistry Indonesia, 2018)
Sella turcica is an anatomic point in the cephalometric tracing of orthodontic treatment. The formula for body mass index (BMI) is calculated by using the height and weight of an individual. Objective: To evaluate the size and morphology of the sella turcica in healthy, overweight, and obese patients. Methods: The 66 individuals (24 males and 42 females; mean age, 15.05 ± 1.61 years) selected for the study were divided into three groups: obese; overweight; and healthy, according to the BMI percentile classification. The length, diameter and depth measurements of the sella turcica were measured on a lateral cephalometric radiograph. Results: No statistically significant differences were found among the groups, although the length, diameter, and depth of the sella turcica were higher in healthy individuals (P > 0.05). Moreover, the normal sella turcica, compared with other sella turcica variations, was more common in 64.7% of the healthy patients, 61.1% of the overweight patients, and 64.3% of the obese patients. Conclusions: Normal sella turcica is more common than other types of sella turcica. In addition, no significant difference was found among the groups in terms of length, diameter, and depth of the sella turcica.